Faktor yang Berhubungan dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Tarus - Retna H.M. Timo; Ribka Limbu; Petrus Romeo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Introduction: Diarrhea is one of the most common diseases affecting children worldwide. Diarrhea is a condition when the sufferer defecates more often than usual, namely defecating more than 3 times a day and the diarrhea sufferer's stool is thinner than usual. Puskesmas Tarus is one of the Puskesmas in Kupang Regency with the highest data on diarrhea cases in 2021 compared to other Puskesmas, namely 132 cases of diarrhea in toddlers. In 2022 diarrhea cases increased, namely 139 until 2023 it continued to increase to 145 diarrhea patients in children under five. Methods : This type of research and research design is quantitative research with Cross Sectional design. the population in this study were all mothers of toddlers in the Tarus Puskesmas Working Area. The population of mothers who have toddlers is 2,110 people. The sampling method is determined by simple random sampling, with mothers or respondents who have toddlers totaling 66 people. Data analysis was performed with the Chi-Square statistical test. Results: The results showed that there was a significant relationship between maternal knowledge (ρ=0.034), hand washing behavior (ρ=0.022), ownership of healthy latrines (ρ=0.007), availability of clean water (ρ=0.029) with the incidence of diarrhea in toddlers in the Tarus Health Center Working Area. Conclusion: It is recommended for mothers to maintain personal hygiene before doing or giving activities to toddlers.